An analysis of dam breaching caused by flow overtopping - Sompong Chamgramol; Tawatchai Tingsanchali; Kubo, Naritaka; Sutat Weesakul; Asian Institute of Technology; Royal Thai Govenment (Pathum Thani : Asian Institute of Technology, 1998)
Flood waves due to sudden outflow through dam breach section cause severe damages downstream of the dam. An accurate estimation of outflow through the dam breach section is important as it is the upstream boundary condition for flood routing toward the downstream direction. The height of peak of flood wave and travel time of the flood wave, if known properly, can be used as a guide for evacuation preparation which can significantly reduce the downstream damage and losses of lift. Model dam made of medium sand with Dso = 0.65 mm. was built in a 1 m. wide and 40 m long flume with horizontal bed and transparent walls on both sides. Six experimental runs were conducted. The upstream slope of the dam is fixed at 1V:3H but the downstream slope is varied from 1V:3H to 1V:2.5H and 1V:2H for Run No.I, 2 and 3 in which the height of the dam is 0.55 m. In Run No.4, the setup is the same as Run No.2 but the dam height is changed to 0.80 m. In Run No.5 and 6, sand of D50 = 0.85 mm. is used and the dam height is 0.55 m. The downstream slope is 1 V:3H and 1 V:2H. The upstream inflow to the reservoir is 9. 3 lps for Run No. 1to4 and 7.8 lps for Run No.5 and 6. The physical model dam shows that the breach starts at the center of dam crest and the overtopping flow causes the breach channel along the downstream face of the dam to enlarge to a larger channel. In addition to the effect of breach enlargement, the collapse of the breach side wall or mass failure accelerates the lowering of the dam crest and the total failure of the dam. During the erosion process, the dam crest propagates in the upstream direction in which the crest elevation reduces exponentially with time and distance. The geometry of breach section and the overtopping discharge can be correlated by a power law. Lastly, the MIKE-11 dambreak model developed by the Danish Hydraulic Institute is used to simulate the dam breaching section geometry and the overtopping discharge. It is found that the MIKE-11 model gives a very underestimated result compared to the experiments.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1998
Keywords: Dam failures